Fundamental manufacturing processes sampler - Society of Manufacturing Engineers; John Wiley & Sons ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2004)
Provides manufacturing process lessons and interactive quiz plus a glossary to define the terms
Code no : DV03PUB122
Title from title screen
Keywords: Manufacturing processing; Metal-cutting; Milling machinery; Milling (Metal-work)